Chinese Medicine Combined With EGFR-TKIs Prolongs Progression-Free Survival and Overall Survival of Non-small Cell Lung Cancer (NSCLC) Patients Harboring EGFR Mutations, Compared With the Use of TKIs Alone - Wang, Yujia; Wu, Guoyu; Li, Ru; Luo, Yingzhe; Huang, Xingmei; He, Lifang; Zhong, Huihui; Xiong, Shaoquan (Frontiers in Public Health, 2021)
Objective To explore the efficacy comparison between epidermal growth factor receptor-tyrosine kinase inhibitor (EGFR-TKIs) combined with Traditional Chinese Medicine (TCM) and single EGFR-TKIs for advanced nonsmall-cell lung cancer (NSCLC). Methods A total of 91 NSCLC patients with EGFR mutation were devided into experimental group and control group (in a ratio of two to one), to receive TCM and EGFR-TKIs (61 cases) or single EGFR-TKIs (30 cases). Patients in control group took EGFR-TKIs and experimental group took EGFR-TKIs plus TCM. Analysed the progression-free survival (PFS), overall survival (OS), disease control rate (DCR) and treatment-related adverse events of two groups. Results The mPFS of the experimental group and the control group were 12.3 months and 8.9 months (P=0.02), the mOS of the experimental group and the control group were 28.2 months and 24.2 months (P=0.02). Subgroup analysis showed that for the patients with exon 19 deletion mutation (19DEL), mPFS between experimental group and control group was 12.7 and 10.1 months respectively (P=0.12). For exon 21 deletion mutation (L858R), the PFS of two groups was 10.8 vs 8.2 months respectively (P=0.03). The subgroup analysis also showed that, for the patients with exon 19 deletion mutation, mOS between the experimental group and the control group was 30.3 and 28.7 months respectively (P=0.19). For exon 21 deletion mutation, the mOS of two groups was 25.5 vs 21.3 months respectively (P=0.01). The DCR of the experimental group and the control group were 93.3% and 80.1% respectively (P=0.77). Grade 3–4 treatment-related adverse events were less common with the experimental group (11.48 %) than the control group (26.67%). Conclusion For NSCLC patients with EGFR mutation, EGFR-TKIs combined with TCM had a certain effect to prolong mPFS and mOS, compared with the use of EGFR-TKIs alone, especially for the patients with L858R. This conclusion have a significant effect on improving the survival of NSCLC patients after EGFR-TKIs resistance. It deserves further study.